Enrichment of live feed Moina micrura with probiotics and its potential in protecting red hybrid tilapia (Oreochromis spp.) against Streptococcus agalactiae infection - Samat, Nur Amalina (2021)
Although many newly-hatched larval fish species are still very much depending on live feeds as a starter diet, the mass production of high-quality live feeds proves to be challenging. The present study aimed to emphasize the utilization of probiotics to promote the production of Moina micrura and subsequently improve red hybrid tilapia survival when being challenged against pathogens. Four potential probiotics identified as Lysinibacillus fusiformis A1, Lysinibacillus fusiformis A2, Bacillus pocheonensis S2, and Lysinibacillus fusiformis Cl3 were used in enrichment assays. After 12 days of incubation, all isolates at 104 and 106 CFU mL-1 were able to enhance the population density, population growth rate, and mean body size of M. micrura. Furthermore, M. micrura enriched with B. pocheonensis S2 at 104 CFU mL-1 had the highest maximum population density (9 ± 0.07 ind./mL) and growth rate (0.4270 ± 0.001/day), whilst M. micrura enriched with L. fusiformis A1 at 104 CFU mL-1 had the longest mean body size (0.87 ± 0.007 mm). In vitro well-diffusion assay was carried out to evaluate the antagonism of all potential probiotics against two freshwater pathogens, Aeromonas hydrophila and Streptococcus agalactiae at three different concentrations of 105, 106, and 107 CFU mL-1. The in vitro study revealed that L. fusiformis A1, L. fusiformis A2, and B. pocheonensis S2 were able to inhibit the growth of both pathogens, whereby B. pocheonensis S2 had the strongest antagonistic activities with inhibition zones ranging from 8 to 18 mm. The ecological consequences of increasing temperature, pH, and abnormal photoperiod on M. micrura enrichment with L. fusiformis A1 and B. pocheonensis S2 were examined for 12 days. It was revealed that M. micrura enriched with B. pocheonensis S2 at 30°C had the highest maximum population density (10 ± 0.2 ind./mL) and number of neonates produced (132 ± 6.43 ind.), meanwhile treatment at 20°C had the best growth rate (0.1863 ± 0.006/day). Similarly, M. micrura incubated with B. pocheonensis S2 at a normal photoperiod of 12L:12D had the highest maximum population density (10 ± 0.3 ind./mL) and number of neonates produced (129 ± 4.58 ind.), meanwhile incubation at 8L:16D had the best growth rate (0.2879 ± 0.0007/day). Next, M. micrura enriched with L. fusiformis A1 at pH 8 had the highest maximum population density (11 ± 0.8 ind./mL), growth rate (0.5508 ± 0.04/day), and number of neonates produced (129 ± 4.36 ind.). Moina micrura and red hybrid tilapia larvae were used as biological models in in vivo bacterial challenge assays to evaluate the efficacy of B. pocheonensis S2 in protecting the host from diseases. Pre-enrichment of M. micrura with B. pocheonensis S2 at 104 CFU mL-1 for 24 h was able to significantly enhance the survival rate of M. micrura after being challenged with S. agalactiae (63 ± 3.33%) and A. hydrophila (63 ± 3.33%). Subsequently, red hybrid tilapia larvae fed with probiotic-enriched M. micrura had a significantly higher survival rate (77 ± 3.3%) than those in the control group (38 ± 4.4%) after being challenged with S. agalactiae following 10 days of experiment. The relative percentage survival rate of the larvae fed with probiotic-enriched M. micrura was recorded at 62.90. Furthermore, the bacterial counts study revealed that B. pocheonensis S2 was able to reduce S. agalactiae load in treated larvae (6.84 ± 0.39 CFU mL-1) in comparison to untreated larvae (7.78 ± 0.09 CFU mL-1), although the result was not statistically significant. In conclusion, due to the need for the increment of M. micrura production and disease resistance of red hybrid tilapia, the application of potential probiotic B. pocheonensis S2 in aquaculture practices worth to be further explored. This isolate has been proven to have a good potential in enriching and enhancing the population growth of M. micrura as well as to act as an excellent therapeutic in improving fish health.